2010
DOI: 10.1029/2009jd012447
|View full text |Cite
|
Sign up to set email alerts
|

Subarctic atmospheric aerosol composition: 3. Measured and modeled properties of cloud condensation nuclei

Abstract: [1] Aerosol particles can modify cloud properties by acting as cloud condensation nuclei (CCN). Predicting CCN properties is still a challenge and not properly incorporated in current climate models. Atmospheric particle number size distributions, hygroscopic growth factors, and polydisperse CCN number concentrations were measured at the remote subarctic Stordalen mire, 200 km north of the Arctic Circle in northern Sweden. The CCN number concentration was highly variable, largely driven by variations in the to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
121
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(126 citation statements)
references
References 71 publications
3
121
1
1
Order By: Relevance
“…Values for SS = 0.1 % are calculated using the unfiltered data that cover the entire measurement period, whereas the values for SS = 0.2, 0.3, 0.5 and 0.7 % are calculated using the filtered data of periods 1, 2 and 3. to indicate a higher organic fraction in these environments. Particularly for Kammermann et al (2010), the lowest values can be explained by the local proximity to the Stordalen mire, which is known to emit biogenic precursors of organic aerosol particles. In a modelling study by Pringle et al (2010), the annual mean κ values at the surface in the region around Tuktoyaktuk were approximately 0.3.…”
Section: Critical Diameter D Crit and Hygroscopicity Parameter κmentioning
confidence: 99%
See 1 more Smart Citation
“…Values for SS = 0.1 % are calculated using the unfiltered data that cover the entire measurement period, whereas the values for SS = 0.2, 0.3, 0.5 and 0.7 % are calculated using the filtered data of periods 1, 2 and 3. to indicate a higher organic fraction in these environments. Particularly for Kammermann et al (2010), the lowest values can be explained by the local proximity to the Stordalen mire, which is known to emit biogenic precursors of organic aerosol particles. In a modelling study by Pringle et al (2010), the annual mean κ values at the surface in the region around Tuktoyaktuk were approximately 0.3.…”
Section: Critical Diameter D Crit and Hygroscopicity Parameter κmentioning
confidence: 99%
“…Summarizing, it can be stated that our observed κ values show no significant dependencies on the SS or the air mass origin that can be resolved with our setup and method. Kammermann et al (2010) (b) Probability density function for κ values at SS = 0.1 % (inferred from the unfiltered CCN and PNSD data of Fig. 4).…”
Section: Critical Diameter D Crit and Hygroscopicity Parameter κmentioning
confidence: 99%
“…1) assuming the surface tension of pure water (Petters and Kreidenweis, 2007;Rose et al, 2008). Due to the surface tension of actual cloud droplets being lower than that of pure water droplets (Facchini et al, 2000), this assumption, although commonly used, typically leads to an overestimation of the N CCN (Kammermann et al, 2010b).…”
Section: Datamentioning
confidence: 99%
“…The HTDMA growth factor distributions showed a certain level of external mixture at the larger dry sizes (75 and 110 nm), and this was more pronounced in wintertime. Kammermann et al (2010) performed a detailed analysis of different methods of predicting the CCN number from HT-DMA and SMPS data, and found that ignoring the growth factor distribution and only using the average growth factor did not have a noticeable influence on the agreement. Additionally, as the growth factors were only measured at discrete dry sizes which were not equal to the d crit , the external mixture may have been implied incorrectly, causing artefacts to the data.…”
Section: Comparison Of D Crit From the Ccn Concentration And Hygroscomentioning
confidence: 99%